VIOLET QURAN HOUSE (RQV)'S DA'WAH STRATEGY IN FORMING ISLAMIC ATTITUDES AND CHARACTERS OF CHILDREN IN THE KARYA INDAH RANTAU PRAPAT ENVIRONMENT - Muliani Nur Susilo; Kamalia (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to examine the da’wah strategies implemented by Rumah Qur’an Violet (RQV) in shaping the attitudes and character of children in the Karya Indah area of Rantauprapat in accordance with Islamic values. Although RQV was established with the objective of addressing Qur’anic illiteracy and fostering noble character among students, the findings reveal a gap between its intended vision and its practical implementation. The current learning process places greater emphasis on Qur’an memorization than on character development, resulting in the persistence of behaviors that are inconsistent with Islamic values, such as the use of impolite language and conflicts among peers. This study employed a descriptive qualitative approach, with data collected through direct observation, interviews, and document analysis. The data were analyzed systematically through the processes of data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of the da’wah strategies implemented by RQV. The findings indicate that RQV plays a significant role in providing educational support through qualified teachers, adequate learning facilities, and relevant religious learning materials. The da’wah strategies implemented include Qur’an memorization activities, worship practices, and weekly religious lectures aimed at instilling values of tranquility, social awareness, and mutual assistance. However, these strategies have not been fully effective in developing a comprehensive Islamic character due to the limited duration of guidance, which is conducted for only three hours per day from Monday to Friday, as well as the insufficient integration of Qur’an memorization programs with moral and character development. Therefore, this study highlights the importance of mentors serving not only as facilitators of memorization achievement but also as role models who foster akhlaq al-karimah through exemplary behavior, positive habituation, and constructive interpersonal interactions. Consequently, a balanced integration of the cognitive aspect of Qur’an memorization and the affective aspect of character formation is essential to achieve the goals of da’wah more effectively and sustainably in producing a Qur’anic generation with noble character.